2020
DOI: 10.1049/el.2019.4263
|View full text |Cite
|
Sign up to set email alerts
|

3D printed waveguide step‐twist with bandpass filtering functionality

Abstract: A novel waveguide step-twist integrated with a bandpass filter is presented in this Letter. The twist is composed of four equally rotated cavities to achieve polarisation rotation and filtering functionalities simultaneously. Such step-twist can achieve a significant reduction in size and weight. The design is demonstrated at Ka-band using waveguide technology and is fabricated using a stereolithography apparatus 3D printing together with metal plating. The device is designed to have a centre frequency of 32 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
(14 reference statements)
0
18
0
2
Order By: Relevance
“…To help maintain a smooth printing process without interior plastic support structures, the slots of the filter's insert section were designed with the blend radius of 4.000 mm and the component was printed at a 65 degree angle with a print-layer thickness of 0.020 mm. Notably, no sidewall slots have been added to the structure for metallization purposes; contrasting a key difference from other monolithic designs ([1], [2]) of this type that are produced with stereolithography 3D-printing.…”
Section: Fabrication and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To help maintain a smooth printing process without interior plastic support structures, the slots of the filter's insert section were designed with the blend radius of 4.000 mm and the component was printed at a 65 degree angle with a print-layer thickness of 0.020 mm. Notably, no sidewall slots have been added to the structure for metallization purposes; contrasting a key difference from other monolithic designs ([1], [2]) of this type that are produced with stereolithography 3D-printing.…”
Section: Fabrication and Measurementsmentioning
confidence: 99%
“…In addition to the these benefits, 3D-printed monolithic designs also allow for the realization of complex structures that may be difficult or impossible to fabricate with traditional milling technologies. For instance, bandpass filter designs that include polarization rotations through the use of twist-like-components have been demonstrated using standard inductive-iris/rectangularresonator configurations [1], [2], as well as with a dual-mode ellipsoidal cavity configuration [3]. Moreover, [4] and [5] have been able to demonstrate multi-component integration techniques in the form of twist/filter/corner combinations and filter-integrated Butler matrices, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The metallization method of resin material is usually electroless plating/copper electroplating, [22][23][24][25] silver deposition, 26 and conductive coatings. 27 Literatures have shown that SLA devices can be metalized, [28][29][30][31][32][33][34][35][36] so that plastic objects can obtain microwave characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it is often manufactured with detached parts and assembled in post‐processing, which unavoidably results in error, air gap and loss. Numerous processing crafts have been adopted in the fabrication of waveguide circuits, such as computer numerical control (CNC)‐metal‐milling technology, sand casting process and 3‐D printing, but post‐processing, such as assembly, 20,21 metal plating 22 and liquid metal filling, 23 is still often indispensable. Even if adopting the so‐called 3‐D printing process, the manufacture of a waveguide structure with internal space is still difficult since the supporter used in printing process would be hardly removed and unexpected concave still appears in the case without supporter 24 …”
Section: Introductionmentioning
confidence: 99%